Group-based behavioural intervention for smoking cessation: is it all in their heads? - Nik Mohamed, Mohamad Haniki (Cambridge University Press, 2011)
In the studies used for the analyses, group counseling is defined as having a minimum of two group meetings, and follow-up of smoking status at least 6 months after the start of the program, with carbon monoxide (CO) validated cessation. Most programs used between six and eight sessions, with the first few sessions devoted to discussion of motivation for quitting, health benefits, and strategies for planning a quit attempt. Participants may also keep records of the number of cigarettes smoked and the triggers for smoking (self-monitoring). Part of the group process also includes discussion and sharing of experiences and problems (intra-treatment social support), as well as on ways to seek appropriate support from friends, colleagues and family (extra-treatment social support).